3D technology of Sony Bloggie has no advantage in decision-making of tennis serve direction: A randomized placebo-controlled study - Liu, S.; Ritchie, J.; Sáenz-Moncaleano, C.; Ward, S. K.; Paulsen, C.; Klein, T. (European Journal of Sport Science, 2017)
This study aimed at exploring whether 3D technology enhances tennis decision-making under the conceptual framework of human performance model. A 3 (skill-level: varsity, club, recreational) × 3 (experimental condition: placebo, weak 3D [W3D], strong 3D [S3D]) between-participant design was used. Allocated to experimental conditions by a skill-level stratified randomization, 105 tennis players judged tennis serve direction from video scenarios and rated their perceptions of enjoyment, flow, and presence during task performance. Results showed that varsity players made more accurate decisions than less skilled ones. Additionally, applying 3D technology to typical video displays reduced tennis players` decision-making accuracy, although wearing the 3D glasses led to a placebo effect that shortened the decision-making reaction time. The unexpected negative effect of 3D technology on decision-making was possibly due to participants being more familiar to W3D than to S3D, and relatedly, a suboptimal task-technology match. Future directions for advancing this area of research are offered.